Disciplinary variations in learning styles and preferences: Implications for the provision of academic English. (February 2019) - Lau, Ken; Gardner, David
Abstract: In higher education, 'disciplines' is a construct that demarcates knowledge and academic identities. Individual disciplines commonly have their own practices, and thus the idea of disciplinary specificity has recently attracted research attention although less so within the area of learning styles and preferences. Drawing on the notion of academic tribes and taxonomy of academic disciplines, we investigate how different disciplinary preferences and learning styles manifest among students attending an academic English course. A questionnaire survey was administered to first-year students at a Hong Kong university, and 278 completed questionnaires were returned by students spanning four disciplines: the soft-pure, soft-applied, hard-pure and hard-applied disciplines. Interviews were conducted with 19 participants to triangulate the questionnaire data. The results show that the respondents had some distinct preferences with regard to the disciplinary characteristics of academic English learning. For example, the soft-pure respondents favoured a solitary mode of learning, while the hard-pure respondents had a predilection for collaborative learning. Moreover, the soft-applied respondents had the strongest commitment to and belief in learner autonomy. These disciplinary variations have strong implications for the design and delivery of academic English courses which recognize this specificity.